THE SEMIOTIC TRANSCODING OF THE EMOTION OF FEAR: A PRAGMASTYLISTIC ANALYSIS OF FEAR IN THOMAS HARRIS’S RED DRAGON AND ITS MULTIMODAL REALIZATION - Ollomurodov Arjunbek Orifjonovich (International Journal of Literature and Language Studies, 2026)
This article investigates the complex linguistic and semiotic mechanisms utilized to encode the emotion of fear within Thomas Harris’s Red Dragon (1981) and evaluates the "intersemiotic transcoding" of these affective markers into the cinematic language of the 2002 film adaptation. By synthesizing principles of cognitive stylistics and multimodal semiotics, the study categorizes how textual fear—encoded through syntactic parataxis, epistemic modality, and somatic lexis—is substituted by visual and auditory signifiers. The research identifies a systematic shift from "linguistic interiority" to "visual focalization," where the novel’s reliance on the reader's cognitive gaps is replaced by a "sensory saturation" of the cinematic frame. Through a rigorous comparison of key narrative nodes, including the Leeds crime scene investigation and the protagonist's empathic shifts, the findings demonstrate that while Harris utilizes linguistic permeability to trigger dread, the film achieves functional equivalence through chromatic dissociation and non-diegetic sound architecture. This study underscores the structural resilience of fear as a trans-medial affect in American psycho-thriller discourse, demonstrating how the "architecture of terror" survives the transition from the symbolic sign-system of literature to the iconic sign-system of cinema.